Pivotal Role of Management of Postpartum Haemorrhage by Using Intrauterine Pack during Caesarean Section - Afroz, Saima; Arzoo, Shabera; Akter, Mst Shamima; Begum, Syeda Anwara; Islam, Md Zakirul; Ahmed, Mainuddin (Eastern Medical College Journal, 2023)
Background: Postpartum Haemorrhage (PPH) is a potentially life-threatening complication after delivery by both vaginal and caesarean section (CS). Different types of management options have been available in clinical settings including the use of oxytocin, prostaglandin analogues, ergometrine, surgical exploration of genital tract, ligation or angiographic embolization of uterine or internal iliac arteries and hysterectomy. Another simple and effective measure to manage PPH is to control the bleeding with intrauterine packing by mop during CS. This intrauterine packing during CS is very easy & quick method to perform and it has pivotal role to save the patient need of major surgical procedures. Objective: To determine effectiveness of uterine packing by mop in control of post-partum hemorrhage, its safety and complications associated with it. Materials and Methods: This study was carried out in Obstetrics & Gynaecology department of Eastern Medical College & Hospital, Cumilla, Bangladesh from January 2020 to July 2020. It was a prospective interventional study. the patients presenting with postpartum haemorhage during CS due to atonic uterus. Patients who had PPH due to genital tract trauma were excluded from this study. Frequencies and proportions of complications were calculated along with rate of successful cessation of bleeding by the use of intrauterine mop. Data was analyzed by SPSS. Results: 100 patients included in the study. Among them 63% were 25-34 years, 26% were 15-24 years, 11% were 35-45 years. 73% patients were p >3 and 27% were p 1-3. 77% patients belong to poor class family, 18% belong to middle class and 5% belong to high class family. These patients went through LUCS and had atonic uterus. Mop was used in those patients and successes rate were 87%. In 13% cases we needed others management. These were 11% case uterotonic drugs, 1% B-Lynch suture, 1% internal iliac artery ligation but none out of 100 patients underwent hysterectomy. Conclusion: Uterine packing by mop effectively controls PPH with fewer complications and its role in emergency obstetric scan not be denied. EMCJ. July 2022; 7(2): 1-5